Influence of coupling agent on the Bound rubber and Dynamic Properties of aluminum sodium silicates filled HNBR composites. Issue 2 (March 2021) - Bi, Weina; Guangshui, Yu; Sun, Jujie; Goegelein, Christoph; Hoch, Martin; Kirchhoff, Joerg; Zhao, Shugao
Abstract: Hydrogenated acrylonitrile-butadiene rubber (HNBR) was used as polymer matrix and micrometer aluminum sodium silicate mineral filler was used as dispersed phase to prepare silicate mineral / polymer composites. Different Triethoxy silane coupling agents were chosen to modify sodium silicate, the vulcanization properties, physical mechanical properties and dynamic mechanical properties of silicate / polymer composites were studied. The results showed that the addition of silane improved the dispersity of sodium aluminum silicate effectively in hydrogenated nitrile rubber. Although the mechanism of actions between VTEO, GLYEO, AMEO silanes and rubber was different, the interactions between filler and rubber were enhanced. These three kinds of triethoxy silane improved the physical and mechanical properties of sodium aluminosilicate / hydrogenated butyronitrile composites obviously.